Pelatihan Pembuatan Website Sebagai Media Pemasaran Produk Bagi Mahasiswa Prodi D4 Tata Boga Jurusan PKK FT-UNM - Wardimansyah Ridwan; Ayu Saputri Bahar; Fitry Purnamasari; Andi Khaerun Niza; Muliani (LITERA ABDI: Jurnal Pengabdian Masyarakat, 2025)
Mastery of digital technology is one of the essential skills in the business world, especially in the field of Culinary Arts, where online product marketing can expand market reach. However, students of the D4 Culinary Arts Study Program, Family Welfare Education Department, Faculty of Engineering, Makassar State University still have limitations in utilizing digital technology, especially in creating websites as a marketing medium. This article aims to describe the implementation of WordPress-based website creation training for 50 students with the aim of improving their skills in marketing products digitally. The training method includes delivering theoretical materials, direct practice, and evaluating results. The training was carried out through several stages, namely introducing basic digital marketing concepts, operating WordPress, creating a simple website, and publishing product content. The results of the training showed that the majority of participants succeeded in creating a functional website as a product marketing medium, with a significant increase in their ability to understand and implement digital marketing strategies. In addition, students appreciated this training as a strategic initial step in supporting the innovation and sustainability of their business.  This activity has a positive impact on students' mastery of digital technology, as well as opening up opportunities for the development of similar training with more complex advanced materials. Thus, this community service is a real contribution in answering the need for students' digital skills in the modern era.